Pembinaan Pelaksanaan Perawatan Jenazah Di Majelis Taklim An-Nur Sepaso Induk - Mahfud Ifendi; Abdurrahim Yunus; Anggra Prima; Ahmad Jazuli; Salsabila Annisa Fitri; Novi Ellawati; Yunida Amini; Abdul Hamid (MAYARA: Jurnal Pengabdian Masyarakat, 2023)
The lack of public willingness, in general, to care for bodies, especially among women, made this the background for this activity. Bearing in mind, the procedure for caring for a corpse should be adjusted according to the sex of the deceased and who will care for him. This coaching activity was carried out at the An-Nur assembly of Sepaso Induk village with the method of mingling servants directly providing coaching, lectures, and practices related to procedures for treating corpses. After this implementation, the participants who took part claimed to have gained a lot of knowledge related to the care of corpses. The enthusiasm of the participants who attended also became a note that similar activities like this should be encouraged among the general public in the future.